2020
DOI: 10.1177/2055102920975969
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psychological aspects, age, and BMI on eating disorder psychopathology among adult males and females with type 1 diabetes

Abstract: This study investigated correlates of eating disorder (ED) psychopathology among adults with type 1 diabetes (T1D). A total of 282 males ( n = 112) and females ( n = 170) with T1D (18–79 years) participated. Overall, psychological aspects (i.e. illness perceptions, coping strategies, insulin beliefs, anxiety, and depression) were associated with ED psychopathology. Associations were generally stronger among females than males. In a regression model, age, BMI, personal control, and anxiety explained 51% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Most studies (n = 19) explored the prevalence of and/or correlates of disordered eating behaviours (including insulin restriction and/or omission) in individuals with T1DM [21,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Three studies focused on sex differences in disordered eating behaviours in individuals with T1DM [22,53,54]. Others compared the nature of disordered eating among individuals with T1DM to individuals with T2DM (n = 4; 55-58) or "healthy" peers without diabetes mellitus (n = 8; 8, 23, 59-64), with one solely focusing on males [23].…”
Section: Research Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies (n = 19) explored the prevalence of and/or correlates of disordered eating behaviours (including insulin restriction and/or omission) in individuals with T1DM [21,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Three studies focused on sex differences in disordered eating behaviours in individuals with T1DM [22,53,54]. Others compared the nature of disordered eating among individuals with T1DM to individuals with T2DM (n = 4; 55-58) or "healthy" peers without diabetes mellitus (n = 8; 8, 23, 59-64), with one solely focusing on males [23].…”
Section: Research Focusmentioning
confidence: 99%
“…Rates of insulin restriction and/or omission in males with T1DM. Of the 33 quantitative papers, (25 samples), where insulin restriction and/or omission was identified among males with T1DM [21-23, 27, 35-39, 42, 43, 45, 50, 52-56, 58, 61, 65-70, 77], interpretable point estimate rates ranged from 1.4% [21,35] to 76% [52][53][54]75]. Fourteen quantitative studies reported no males restricting and/or omitting insulin for weight and/or shape control [30-32, 40, 41, 44, 46-49, 51, 59, 60, 64, 78].…”
Section: Quantitative Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One in two studies found that elevated serotonin levels were correlated with a lower risk of suicide [ 3 ]. Psychopathology linked to physical conditions and the onset of chronic diseases is receiving growing attention since scientific evidence is confirming the need to consider psychic manifestations due to medical conditions as well as symptoms occurring due to the role of psychological domains and phenomena [ 4 , 5 , 6 , 7 , 8 , 9 ]. Serum serotonin values over 400 μg/L are usually associated with metastatic abdominal carcinoid tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin omission is associated with impaired glycemic control and a threefold increase in mortality (Goebel‐Fabbri et al, 2008). Also, diabetes‐specific illness perceptions (Wisting, Rø, Skrivarhaug, Dahl‐Jørgensen, & Rø, 2019; Wisting, Siegwarth, Skrivarhaug, Dahl‐Jørgensen, & Rø, 2020) and diabetes distress (Saßmann et al, 2020; Strandberg, Graue, Wentzel‐Larsen, Peyrot, & Rokne, 2014) have been associated with ED psychopathology and poor glycemic control among individuals with type 1 diabetes, especially young females. Females who have diabetes and are in their late adolescence or early adulthood appear to be at particular risk for developing ED (Wisting, Skrivarhaug, Dahl‐Jørgensen, & Rø, 2018).…”
Section: Introductionmentioning
confidence: 99%